2002
DOI: 10.1111/j.1365-2621.2002.tb08819.x
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase Catalyzed Reactions: Impact on Food Applications

Abstract: Transglutaminases can perform various reactions that are based on cross-linking, acyl-transfer and deamidation. These enzymes are found in many different organisms where they have very specific roles. The basic reaction mechanism of these transglutaminases is similar. The reactions catalyzed by transglutaminases have proven to be useful in production of different kinds of protein ingredients and food products. In this review, we will show important aspects of transglutaminase cross-linking in respect to substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
174
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(187 citation statements)
references
References 52 publications
(15 reference statements)
0
174
0
3
Order By: Relevance
“…Chambi and Grosso (2006) was able to create an edible film of a combination of B-type bovine gelatin with casein through an enzymatic process.The enzyme that was often used as a crosslinked agent among the two proteins was transglutaminase enzyme (TGse, proteinglutamine c-glutamyl transferase, EC 2.3.2.13) catalyzed the reaction of acyl transfer between the γ-glutamine residues carboxiamide group (acyl donor) and the eamino lysine residues (acyl acceptor), resulting in the formation of (e-γ -glutamyl) lysine intra-and intermolecular cross-linked protein (De Jong and Koppelman, 2002). The formation of crosslinking did not reduce the nutritional quality of the food as lysine residues remain available for digestion (Yokohama et al, 2004).…”
Section: The Properties Of Edible Film Derived From Bovine Split Hidementioning
confidence: 99%
“…Chambi and Grosso (2006) was able to create an edible film of a combination of B-type bovine gelatin with casein through an enzymatic process.The enzyme that was often used as a crosslinked agent among the two proteins was transglutaminase enzyme (TGse, proteinglutamine c-glutamyl transferase, EC 2.3.2.13) catalyzed the reaction of acyl transfer between the γ-glutamine residues carboxiamide group (acyl donor) and the eamino lysine residues (acyl acceptor), resulting in the formation of (e-γ -glutamyl) lysine intra-and intermolecular cross-linked protein (De Jong and Koppelman, 2002). The formation of crosslinking did not reduce the nutritional quality of the food as lysine residues remain available for digestion (Yokohama et al, 2004).…”
Section: The Properties Of Edible Film Derived From Bovine Split Hidementioning
confidence: 99%
“…Gelatin can be gelled by cooling a biopolymer solution below the helixecoil transition temperature to promote the formation of helices and hydrogen bond cross-links (Izmailova et al, 2004). Enzymes such as transglutaminase can also be used to form covalent cross-links between amino acids on various protein substrates (DeJong & Koppelman, 2002), which has recently been used to form biopolymer delivery systems for lipophilic components (Huppertz & de Kruif, 2008;Song, Zhang, Shi, & Li, 2010).…”
Section: Biopolymer Particles: Single Biopolymer Typementioning
confidence: 99%
“…However, transglutaminase is a kind of enzyme which can catalyze the covalent cross linking reactions between proteins to form high molecular weight (MW) biopolymers. De Jong & Koppelman (2002) reported that transglutaminase catalyzes acyltransfer reactions between λ-carboxyamide groups of glutamine residues (acyl donor) and ε-amino groups of lysine residues (acyl acceptor), resulting in the formation of ε-(λ-glutaminyl) lysine intra and intermolecular cross-linked proteins. The reaction catalyzed of glutamyltransferases is shown in Figure 2 (Yee et al, 1994) Polymerization using transglutaminase has been investigated with various protein sources including casein, soy proteins and gelatin, where different responses in gel strength were dependent on the reaction conditions and on the different protein sources (Sakamoto et al, 1994).…”
Section: Modification Of Protein-based Edible Films By Enzymatic Treamentioning
confidence: 99%